Floristic Diversity in Plantations of Tectona grandis L.f. of Different Ages - Burgos Cevallos, José Antonio (2026)
Agroforestry is recognized as a sustainable production system that enhances carbon sequestration and efficient nutrient cycling, with its ecological benefits including increased plant diversity, a key factor in maintaining ecosystem health. This study aimed to assess floristic diversity in Tectona grandis plantations aged 2 to 18 years during the rainy season in the cantons of Pichincha, Palenque, and Balzar (Ecuador). The Jaccard similarity index, as well as the Shannon-Wiener and Simpson diversity indices, were applied for analysis. Results from the Shannon-Wiener index revealed high diversity in the localities of La Colina, La Párraga, Cerro Verde, La Reserva, and San Agustín, while the Simpson index indicated moderate diversity in La Reserva, Cerro Verde, La Párraga, La Colina, San Agustín, and Río Grande-Pichincha. The progressive increase in plant diversity observed in the plantations suggests a significant improvement in ecosystem functionality and resilience, reinforcing the potential of agroforestry systems as a sustainable management strategy.